Interactive Force Control Based on Multimodal Robot Skin for Physical Human−Robot Collaboration. (15th July 2021) - Armleder, Simon; Dean-Leon, Emmanuel; Bergner, Florian; Cheng, Gordon
Abstract : This work proposes and realizes a control architecture that can support the deployment of a large‐scale robot skin in a Human‐Robot Collaboration scenario. It is shown, how whole‐body tactile feedback can extend the capabilities of robots during dynamic interactions by providing information about multiple contacts across the robot's surface. Specifically, an uncalibrated skin system is used to implement stable force control while simultaneously handling the multi‐contact interactions of a user. The system formulates control tasks for force control, tactile guidance, collision avoidance, and compliance, and fuses them with a multi‐priority redundancy resolution strategy. The approach is evaluated on an omnidirectional mobile‐manipulator with dual arms covered with robot skin. Results are assessed under dynamic conditions, showing that multi‐modal tactile information enables robust force control while at the same time remaining responsive to a user's interactions. Abstract : The sense of touch is an important aspect of natural collaboration between humans and robots. This work extends the capabilities of robots during dynamic interactions with humans by using the tactile feedback of a large‐area skin system. The implemented control architecture is validated on a mobile manipulator and enables stable force control while performing a collaborative task with a human.